Twenty-Year Trajectory-Patterns of Percentage Energy From Dietary Fat vs. Carbohydrate Throughout Adult Life and Associations With Cardio-Metabolic Disease and All-Cause Mortality - Guo, Xiaoyu; Xu, Xiaoqing; Gao, Jian; Wang, Weiqi; Hou, Wanying; Wu, Xiaoyan; Sun, Changhao; Li, Ying; Han, Tianshu (Frontiers in Nutrition, 2021)
Background: The health impacts of dietary fat-to-energy ratio (FER) compared to carbohydrate-to-energy ratio (CER) are widely discussed topics in public health. This study aimed to assess the health impacts of FER and CER by establishing trajectory-patterns of FER and CER over the course of adult life. Methods: This study used the weighted longitudinal data of the China Health and Nutrition Survey, including eight surveys from 1991 to 2011. The trajectories of FER and CER were determined via latent class trajectory modeling. The trajectories were then cross-grouped into different trajectory-patterns. Multivariate Cox regression models were used to assess the relationship between these trajectory-patterns and cardio-metabolic diseases and all-cause mortality. 10,926 adults with a total of 50,693 observations across eight surveys were included. Results: Compared to the trajectory-pattern of persistently low-FER (increased from 10% to 20%) and moderate-CER (stable and ranging from 55% to 65%) over the adult life-course, the two trajectory-patterns that showed changing to high-FER and low-CER were significantly associated with obesity (HR 1.83 [95% CI, 1.10-3.04]; HR 1.46 [95% CI, 1.02-2.17]), diabetes (HR 1.80 [95% CI, 1.03-3.16]; HR 1.49 [95% CI, 1.01-2.25]), and all-cause mortality (HR 2.29 [95% CI, 1.35-3.87]; HR 1.62 [95% CI, 1.18-2.22]). In contrast, the trajectory-pattern of a persistently low-FER and high-CER diet was not associated with obesity (HR 1.19 [95% CI, 0.82-1.17]), diabetes (HR 1.41 [95% CI, 0.98-2.02]), cardiovascular-disease (HR 1.48 [95% CI, 0.91-2.39]), and all-cause mortality (HR 1.23 [95% CI, 0.94-1.61]). Conclusions: This study indicates that changing to a high-FER and low-CER diet over the course of adult life was significantly associated with obesity, diabetes, and all-cause mortality in the Chinese adult population. In addition, low-FER and high-CER were not associated with cardio-metabolic disease and all-cause mortality. These observations may provide insights into nutritional policy and dietary guidelines.